EFEKTIVITAS LKPD BERBASIS ETNOMATEMATIKA UNTUK MENINGKATKAN KEMAMPUAN PEMECAHAN MASALAH DAN MOTIVASI BELAJAR - Fitriasih Eka Destareiza; Nuryadi, Nuryadi; Supriyanti, Supriyanti (TRANSFORMASI, 2024)
This research aims to determine the effectiveness of ethnomathematics-based student worksheets teaching materials to improve students' problem-solving abilities and learning motivation. This research was conducted using a pretest-posttest control group design, with an experimental research type. The research population was students in class VII of SMP Negeri 1 Sedayu, while the sample was students in class VII B and VII E. Data collection was carried out using test and questionnaires. Data analysis was carried out using Wilcoxon Ranked-Signed Test, Mann-Whitney U Test, and mean difference test. This method was used because the data obtained was not normally distributed. The results of the research show that the use of ethnomathematics-based student worksheets is effective in increasing students’ problem solving abilities and learning motivation. Further research can be carried out using a larger number of samples or determining a sample with a normal distribution so that the research results can be generalized to the population.